Assessment of the application for renewal of authorisation of Biosprint® (Saccharomyces cerevisiae MUCL 39885) for dairy cows and horses. (28th November 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the assessment of the application for renewal of authorisation of the product Biosprint ® ( Saccharomyces cerevisiae MUCL 39885) as a feed additive for dairy cows and horses. S. cerevisiae is considered by EFSA to have qualified presumption of safety (QPS) status. The applicant has provided data demonstrating that the additive currently in the market complies with the conditions of authorisation. The Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) Panel confirms that the use of Biosprint ® under the current authorised conditions of use is safe for the target species, the consumers and the environment. The additive is considered as a potential skin and eye irritant and skin/respiratory sensitiser. There is no need to assess the efficacy of Biosprint ® in the context of the renewal of the authorisation.